Women in Management and the Gender Pay Gap - Virginia Sondergeld; Katharina Wrohlich (Institute of Labor Economics (IZA), 2023)
We analyze the impact of women's managerial representation on the gender pay gap among employees on the establishment level using German Linked-Employer-Employee- Data from the years 2004 to 2018. For identification of a causal effect we employ a panel model with establishment fixed effects and industry-specific time dummies. Our results show that a higher share of women in management significantly reduces the gender pay gap within the firm. An increase in the share of women in first-level management e.g. from zero to above 33 percent decreases the adjusted gender pay gap from a baseline of 15 percent by 1.2 percentage points, i.e. to roughly 14 percent. The effect is stronger for women in second-level than first-level management, indicating that women managers with closer interactions with their subordinates have a higher impact on the gender pay gap than women on higher management levels. The results are similar for East and West Germany, despite the lower gender pay gap and more gender egalitarian social norms in East Germany. From a policy perspective, we conclude that increasing the number of women in management positions has the potential to reduce the gender pay gap to a limited extent. However, further policy measures will be needed in order to fully close the gender gap in pay.
Keywords: J16; J31; J71; 330; gender pay gap; women in management; board diversity; two-way fixed effects; linked employer-employee data